DETERMINAN KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR DI INDONESIA; EKSPLORASI INTELLECTUAL CAPITAL DAN CORPORATE GOVERNANCE - Dewa Ayu Oki Asta Rini; - Akram; Lilik Handajani (InFestasi, 2016)
The aim of research is to know the intellectual capital, corporate governance effect and company’s characteristic toward financial archievment at manufacture company by using partial lest square (PLS). The research was apllied in 38 manufacture company (28,78 % from 132 companies) by using secondary data in front of financial and annual report from 2011 to 2013. The result indicated that intellectual capital has positive effect toward financial achievment, which indicated that the company hasi seriousness to give value by using high VAICTM and increase the intangible asset thorugh MBIC. Corporate governance has so significant effect  toward financial achievment, that indicate the how level of suitability in applying corporate governance. Practice toward the entirely principle of OECD (2004). Corporate governance pratice that the refer to OECD (2004) principle is still dominated by the role of stakeholder in corporate governance. The transparancy and responsibility of committe. In the future, the company must give more right of shareholder’s  and the equitable treatment to  shareholder